Adsorption equilibrium of water vapor on activated carbon and alumina and carbon and alumina impregnated with hygroscopic salt - Ioan Solomon (2013)
The adsorption equilibrium of water vapor on different adsorbent materials has been studied. Small grains of commercial activated carbon and alumina, with a diameter of d(g) = 1.5 x 10(-3) m, were impregnated with a hygroscopic salt (calcium chloride) to improve the performance of these materials. The main characteristics of the new composite materials were obtained by adsorption/desorption of nitrogen at 77 K and salt distribution on the adsorbent surface was shown using scanning electron microscopy. The adsorption equilibrium isotherms of water vapor were measured by a gravimetric system at 2 different temperatures in the case of alumina and impregnated alumina (303 K and 313 K) and 1 temperature (303 K) in the case of activated and impregnated carbon. The impregnated material samples presented the highest adsorption capacity on the entire pressure range. The experimental points obtained for the activated carbon and alumina and the impregnated alumina were fitted with the Dubinin-Astakhov equation while the Langmuir equation was used to fit the impregnated carbon data.